R & D Philippines. - National Science and Technology Authority (Bicutan, Taguig, Metro Manila Scientific Clearinghouse and Documentation Services, National Science & Technology Authority, 1983)
Annual.
Absorbed: Selected R & D projects (completed)
Mimeographed.
Keywords: Science -- Philippines; Technology -- Philippines